SERIKAT PEKERJA DALAM KEWAJIBANNYAMERUMUSKAN PEMBUATAN DAN PELAKSANAAN PERJANJIAN KERJA BERSAMADENGAN MANEGEMEN (IMPLEMENTASI UU NOMOR 21 TAHUN 2000) - Arno, Abdul Kadir (Al-Amwal : Journal of Islamic Economic Law, 2018)
The union as a container for aspiration struggle for all workers has a very important function and role for the lives of workers in the world of work, especially in the creation and implementation of Collaborative Work Agreements containing the arrangements of work requirements, rights and obligations that are often regarded as formality in the implementation of finding barriers, both from workers and from employers. Implementation of the Collaborative Working Agreement has in principle worked well even though there are some agreements that are not implemented by both parties. Failure of agreement by both parties should not result in a dispute over the employment relationship as it can always be done with the consideration of reaching an agreement. The lack of optimal role of Trade Unions in advocating workers' rights, ignorance and lack of workers' awareness of workers' rights, and low Worker Resources is an obstacle in the implementation of the Collective Labor Agreement